2019
DOI: 10.30773/pi.2019.0168
|View full text |Cite
|
Sign up to set email alerts
|

Development of Brief Post-Traumatic Stress Disorder Rating Scale for Sexual Violence Victims

Abstract: The purpose of this study was to develop a brief rating scale of post-traumatic stress disorder (PTSD) symptoms among sexual violence victims. We analyzed the data from 195 victims and 220 non-victims to select meaningful items from the original PTSD rating scales. We also examined the validity of the brief scale by assessing internal consistency and ROC curves. The optimal cutoff scores for each brief scales were obtained. The results showed that a different approach may be required for early intervention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A description of the modifications was reported in Kerr et al (2021) . Previous studies incorporating the full PROPS measure with community-based samples have reported average scores ranging from 6.0 to 18.3 ( Chung et al, 2019 ; Greenwald & Rubin, 1999 ) out of a possible score range of 0–60. The clinical cutoff in the full scale is 16; however, due to scale modifications, we were unable to compute a comparable cutoff in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…A description of the modifications was reported in Kerr et al (2021) . Previous studies incorporating the full PROPS measure with community-based samples have reported average scores ranging from 6.0 to 18.3 ( Chung et al, 2019 ; Greenwald & Rubin, 1999 ) out of a possible score range of 0–60. The clinical cutoff in the full scale is 16; however, due to scale modifications, we were unable to compute a comparable cutoff in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…First, as shown in Figure 2(a) and (c), half of the 10 major risk factors for adult women were related to mental health (i.e. anxiety symptoms, 38 alcohol use disorder symptoms, 39 posttraumatic stress disorder (PTSD) symptoms, 40 depressive symptoms, 38 and obsessive-compulsive disorder ). Second, compared to adult women, as shown in Figure 2(b) and (c), half of the 10 major risk factors for adolescent women were related to interpersonal experiences and needs.…”
Section: Resultsmentioning
confidence: 99%